Research handbook on European union citizenship law and policy : navigating challenges and crises - Kostakopoulou, Theodora; Thym, Daniel (Research handbooks in European law series, 2022)
"This Research Handbook provides a panoramic guide to the study and research of EU citizenship and its development within a challenging environment characterised by restrictive access to social benefits, Brexit, Euroscepticism and Covid-19. It combines theoretical perspectives with analyses of both the existing and future rights, duties and social protection that EU citizens ought to enjoy in a democratic and principled European Union. Featuring expert contributions from scholars both within and outside the discipline of law, the Research Handbook focuses on contemporary challenges facing the EU, such as Brexit, the erosion of rights and issues of constitutional choice for the citizens and governments of Europe, and highlights the reality of incomplete implementation of EU law and the role of the Court of Justice of the EU. A wide range of topics are discussed, featuring, but not limited to, differentiation, EU citizenship and nationality, the European Pillar of Social Rights, academic freedom and restrictions in free movement of persons. The book also applies a forward thinking approach by examining the promise of EU citizenship and the institutional reforms one might envisage in the future. Offering a thought-provoking contribution to ongoing debates and studies in the fields of EU citizenship, European internal market law and policy and European integration, this Research Handbook will be key reading for researchers, academics and postgraduate students in the fields of law, political science, EU studies, and sociology"--